Composite diaphragm and preparation method thereof, and battery and object having the same
By coating nanomaterials and PVDF slurry on the electrospinned film base film of the lithium-ion battery separator to form a composite separator, the problems of low thermal safety performance and insufficient mechanical performance of traditional separators are solved, and higher conductivity is achieved , liquid absorption and heat shrinkage resistance.
Patent Information
- Application Number
- CN202111484823.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-07
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2041-12-07
AI Technical Summary
Traditional microporous polyolefin separators have problems such as low thermal safety performance and reduced charge and discharge cycle performance in lithium-ion batteries, and a single electrospinning film material has problems such as insufficient mechanical properties and irregular structure.
An electrospinned film is used as the base film, and nanomaterial is coated on one side and PVDF slurry is coated on the other side to form a composite separator. The composite separator improves electrolyte affinity through the polymer mixture in the electrospinning liquid, nanomaterials improve conductivity, and PVDF slurry improves liquid absorption and heat shrinkage resistance.
The mechanical strength, conductivity, liquid absorption and heat shrinkage resistance of the lithium-ion battery separator are improved, thereby improving the thermal safety performance and charge and discharge cycle performance of the battery.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a composite diaphragm and a preparation method thereof, and a battery and an object having the same. Background Art
[0002] Lithium-ion battery separator is an important component to ensure the safety performance of lithium-ion batteries. Its main function is to provide microporous channels to conduct lithium ions in liquid electrolytes while insulating electrons. The structure and performance of the separator have a great influence on the charge and discharge capacity and cycle life of lithium-ion batteries. Traditional microporous polyolefin separators have high mechanical properties and good electrochemical stability, but the separator has a high dielectric constant, a maximum porosity of about 40%, a low melting point, and a low liquid absorption rate. These shortcomings will lead to low thermal safety performance of the battery and reduced charge and discharge cycle performance.
[0003] Electrospun fiber membranes have excellent properties such as large specific surface area, high porosity, and small pore size. Their application as lithium-ion battery separators has attracted widespread attention from researchers. However, due to the defects of nano-diaphragm materials prepared from single polymer materials, such as PVDF nanofiber membranes, although they have good mechanical properties, their structure is regular and the crystallinity is high, which affects the ionic conductivity; PAN is easy to spin and has high ionic conductivity, but it is soft and prone to static electricity after film formation, and has poor mechanical properties. Therefore, the mechanical properties of fiber membranes are often improved by adding inorganic nanoparticles, mixing different polymers, coaxial electrospinning, multi-layer composites, heat treatment or cross-linking modification. CN201610062823.6 discloses a method for preparing a high thermal stability anti-overcharge battery separator by electrospinning. By adding nano-titanium dioxide to reduce the particle size of the active substance, the explosion caused by overheating of the battery and short circuit of the battery due to increased current is prevented, and the service life of the battery is increased. However, the addition of nano-titanium dioxide will affect the membrane's permeability and wetting properties to the electrolyte and the mechanical properties of the membrane. Summary of the invention
[0004] The purpose of the present application is to provide a composite membrane to overcome the defects of the single electrospun membrane in the prior art, improve the mechanical strength of the electrospun membrane, and control the pore size.
[0005] To achieve the above purpose, the embodiment of the present application adopts the following technical solution: a composite diaphragm, comprising:
[0006] A base film, wherein the base film is an electrospun film, and the electrospun film is made by electrospinning an electrospinning solution, wherein the electrospinning solution includes a polymer mixture;
[0007] A first coating layer, wherein the first coating layer is disposed on one side surface of the base film, and the first coating layer is formed by coating with a nano coating;
[0008] The second coating layer is arranged on the other side surface of the base film, and the second coating layer is formed by spraying PVDF slurry.
[0009] In the above technical scheme, the embodiment of the present application uses an electrospun film as a base film, and the electrospun film is electrospun in a miscible manner, wherein the polymer mixture has the characteristics of good hydrophilicity and high surface energy, which can improve the affinity of the lithium battery separator to the electrolyte. In addition, the present application also coats a nanomaterial on one side of the electrospun film, and the nanomaterial has the characteristics of high room temperature ionic conductivity, which can improve the conductivity of the lithium battery separator, and at the same time coats PVDF slurry on the other side of the base film to improve the liquid absorption performance and heat shrinkage resistance of the composite separator.
[0010] Further, according to an embodiment of the present application, the polymer mixture includes polyvinylidene fluoride and polyacrylonitrile.
[0011] Further, according to an embodiment of the present application, the mass ratio of the polyvinylidene fluoride to the polyacrylonitrile is (1-9): (1-9).
[0012] Further, according to an embodiment of the present application, the nano coating has a NASICON type structural system.
[0013] Further, according to an embodiment of the present application, the nano coating is LATP slurry.
[0014] Further, according to an embodiment of the present application, the LATP slurry contains 10-25wt% of LATP nanomaterial.
[0015] Further, according to an embodiment of the present application, the thickness of the first coating layer is 0-5 μm.
[0016] Further, according to an embodiment of the present application, the thickness of the second coating layer is 0-5 μm.
[0017] Further, according to an embodiment of the present application, the PVDF slurry contains 1-10 wt % of a base material.
[0018] Further, according to an embodiment of the present application, the base material includes PVDF powder, a water-based adhesive, a surfactant, and a dispersant.
[0019] In order to achieve the above object, the present application also discloses a method for preparing a composite diaphragm, comprising the following steps:
[0020] Preparation of electrospinning film: drying the powdered polymer mixture and adding it to a solvent N,N-dimethylformamide, stirring to fully disperse it to obtain an electrospinning solution, and performing electrospinning in an electrospinning device to obtain the electrospinning film;
[0021] Preparation of nano coating: preparing a mixed solution of DMF and anhydrous ethanol, adding the LATP nanomaterial into the mixed solution, stirring and dispersing, and preparing the nano coating;
[0022] Preparation of PVDF slurry: heat and stir the dispersant and distilled water at 40-80°C for 10-60 minutes to completely mix them, add PVDF powder to the mixed material, stir for 0.5-4 hours to obtain a PVDF dispersion, then add an aqueous binder and a surfactant, stir evenly, and filter with a magnetic filter and a 100-mesh filter to obtain the PVDF slurry;
[0023] Preparation of the composite membrane: coating the nano coating on one side of the electrospun film, and spraying the PVDF slurry on the other side of the electrospun film to obtain the composite membrane.
[0024] Further, according to an embodiment of the present application, the electrospinning equipment adopts a spinning rate of 0.2-1.2 ml / h, a voltage of 14-20 KV, an ambient humidity of ≤30%, a distance from the spinning nozzle to the receiving plate of 10-20 cm, and is collected by a drum and dried at 50-80°C for 1-3 hours.
[0025] Further, according to an embodiment of the present application, the LATP nanomaterial is prepared by the following method:
[0026] Li2CO3, AlOOH, TiO2, and NH4H2PO4 powders are added into anhydrous ethanol, and then mixed on a planetary ball mill to obtain a precursor material; the precursor material is calcined in a muffle furnace, and the LATP nanomaterial is obtained through grinding and sieving.
[0027] Further, according to an embodiment of the present application, the molar ratio of Li2CO3:AlOOH:TiO2:NH4H2PO4 in the precursor material is 1.3:0.3:1.7:1.
[0028] Further, according to an embodiment of the present application, the temperature in the muffle furnace is first increased to 200-300°C at a heating rate of 2-5°C / min and calcined for 2-4h, then increased to 600-800°C and calcined for 3-5h, and then naturally cooled to room temperature.
[0029] Further, according to an embodiment of the present application, the mass ratio of DMF to anhydrous ethanol is 2:1.
[0030] Further, according to an embodiment of the present application, in the PVDF slurry, the mass ratio of PVDF powder, aqueous adhesive, surfactant and dispersant is 65-85:3-10:1.5-5:8-20.
[0031] In order to achieve the above-mentioned purpose, an embodiment of the present application further discloses a battery having a diaphragm, wherein the diaphragm is made of the composite diaphragm as described above.
[0032] In order to achieve the above-mentioned purpose, an embodiment of the present application further discloses an object, characterized in that the object has a battery as described above.
[0033] Further, according to an embodiment of the present application, the object is an electronic product or a means of transportation.
[0034] Compared with the prior art, the present application has the following beneficial effects: the present application uses an electrospun film as a base film, and the electrospun film is electrospun in a miscible manner, wherein the polymer mixture has the characteristics of good hydrophilicity and high surface energy, and can improve the affinity of the lithium battery separator to the electrolyte. In addition, the present application also coats a nanomaterial on one side of the electrospun film, and the nanomaterial has the characteristics of high room temperature ionic conductivity, which can improve the conductivity of the lithium battery separator, and at the same time coats a PVDF slurry on the other side of the base film, thereby improving the liquid absorption performance and heat shrinkage resistance of the composite separator. DETAILED DESCRIPTION
[0035] In order to make the purpose and technical solution of the present invention clearly and completely described, and the advantages more clearly understood, the embodiments of the present invention are further described in detail below. It should be understood that the specific embodiments described herein are part of the embodiments of the present invention, rather than all of the embodiments, and are only used to explain the embodiments of the present invention, and are not used to limit the embodiments of the present invention. All other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] In the description of the present invention, it should be noted that the terms "center", "middle", "upper", "lower", "left", "right", "inner", "outer", "top", "bottom", "side", "vertical", "horizontal" and the like indicating directions or positional relationships are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the devices or elements referred to must have a specific direction, be constructed and operated in a specific direction, and therefore cannot be understood as limiting the present invention. In addition, the terms "one", "first", "second", "third", "fourth", "fifth", "sixth" are only used for descriptive purposes and cannot be understood as indicating or implying relative importance.
[0037] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0038] For the purpose of simplicity and illustration, the principles of the embodiments are mainly described by reference to examples. In the following description, many specific details are proposed to provide a thorough understanding of the embodiments. However, it is obvious that for those of ordinary skill in the art, these embodiments may not be limited to these specific details in practice. In some instances, known methods and structures are not described in detail to avoid making these embodiments unnecessarily difficult to understand. In addition, all embodiments can be used in combination with each other.
[0039] The present application discloses a composite diaphragm, comprising a base film and a first coating and a second coating respectively arranged on both sides of the base film. The base film is an electrospinning film, which is made by electrospinning an electrospinning solution, and the electrospinning solution used includes a polymer mixture, which has the characteristics of good hydrophilicity and high surface energy, and can improve the affinity of the lithium battery diaphragm to the electrolyte. In addition, the first coating is formed by coating with a nano coating, and the nano material has the characteristics of high room temperature ionic conductivity, which can improve the conductivity of the lithium battery diaphragm. The second coating is sprayed with PVDF slurry, and there is a void distribution between the PVDF particles, which can improve the liquid absorption capacity of the composite diaphragm and improve its heat shrinkage resistance.
[0040] Furthermore, the polymer mixture includes polyvinylidene fluoride (PVDF) and polyacrylonitrile (PAN), and the mass ratio of the mixture ratio is (1-9): (1-9), preferably 1:1. The diameter of pure PVDF nanofibers is relatively large, the thickness uniformity is slightly poor, and the fibers of the nanofiber membrane are relatively tightly arranged; the diameter of pure PAN nanofibers is small, the thickness is relatively uniform, and the fibers of the nanofiber membrane are relatively loosely arranged. In the present application, as the proportion of PVDF added to the polymer mixture increases, the diameter of the mixed fiber becomes coarser and the porosity decreases. In addition, if the proportion of PVDF added is too large or too small, the fiber diameter distribution range is large, and multiple fibers will be separated from a single fiber. This is due to phase separation of the fibers. When PVDF:PAN=5:5, the thickness of the nanofiber membrane fibers is relatively uniform, indicating that the PVDF and PAN mixture is more uniform and stable under this ratio.
[0041] Secondly, the above-mentioned nano coating is a LATP slurry with a NASICON-type structural system, and the slurry contains 10-25wt% of LATP nanomaterial. Specifically, the structural formula of the LATP nanomaterial is Li 1+x Al x Ti 2-x (PO4)3, with the spatial structure group of R-3C, is a sodium superion conductor NASICON-type solid electrolyte with the characteristics of high room temperature ionic conductivity, wide stable potential window and good thermal stability. The PVDF-PAN electrospinning film is modified by LATP nanomaterials, so that there are a large number of lithium vacancies and lithium gaps on the surface of the composite membrane, which makes Li + The migration of Li + The nano coating has a first coating layer with a thickness of 0-5 μm.
[0042] In addition, the above PVDF slurry contains 1-10wt% of a base material, which includes PVDF powder, a water-based adhesive, a surfactant, and a dispersant. There are cavities between the particles in the PVDF slurry, which is also beneficial to Li + The PVDF material can be embedded and removed, and has good liquid absorption and retention for electrolyte. In addition, based on the characteristics of PVDF materials, the heat shrinkage resistance of the composite diaphragm can be greatly improved, reducing the probability of short circuit caused by positive and negative contact due to shrinkage of the diaphragm, thereby improving the safety performance and cycle life of the battery cell. Furthermore, the thickness of the second coating formed by the PVDF slurry is 0-5μm.
[0043] Finally, the preparation method of the composite membrane comprises the following steps:
[0044] Preparation of electrospinning film: drying the powdered polymer mixture, adding it to the solvent N,N-dimethylformamide, stirring it to fully disperse it, obtaining an electrospinning solution, and electrospinning it in an electrospinning device to obtain the electrospinning film. The electrospinning device uses a spinning rate of 0.2-1.2ml / h, a voltage of 14-20KV, an ambient humidity of ≤30%, a distance of 10-20cm between the spinning nozzle and the receiving plate, collecting it through a drum, and drying it at 50-80°C for 1-3h.
[0045] Preparation of nano coating: prepare a mixed solution of DMF and anhydrous ethanol, add the LATP nano material to the mixed solution, stir and disperse to obtain the nano coating. Wherein, the LATP nano material is prepared by the following method: add Li2CO3, AlOOH, TiO2, and NH4H2PO4 powders to anhydrous ethanol, and then mix them on a planetary ball mill to obtain a precursor material; calcine the precursor material in a muffle furnace, grind and sieve to obtain the LATP nano material. The molar ratio of Li2CO3:AlOOH:TiO2:NH4H2PO4 in the precursor material is 1.3:0.3:1.7:1. The temperature is first raised to 200-300℃ and calcined for 2-4h at a heating rate of 2-5℃ / min in the muffle furnace, and then raised to 600-800℃ and calcined for 3-5h and then naturally cooled to room temperature. The mass ratio of DMF to anhydrous ethanol is 2:1.
[0046] Preparation of PVDF slurry: Heat and stir the dispersant and distilled water at 40-80°C for 10-60 minutes to completely mix them, add PVDF powder to the mixed material, stir for 0.5-4 hours to obtain PVDF dispersion, then add water-based adhesive and surfactant, stir evenly, filter with a magnetic filter and a 100-mesh filter to obtain the PVDF slurry. The mass ratio of PVDF powder, water-based adhesive, surfactant and dispersant is 65-85:3-10:1.5-5:8-20.
[0047] Preparation of the composite membrane: coating the nano coating on one side of the electrospun film, and spraying the PVDF slurry on the other side of the electrospun film to obtain the composite membrane.
[0048] The technical effects of the present application are described below by listing embodiments and comparative examples, but the present application is not limited to these embodiments.
[0049] [Example 1]
[0050] 3g PVDF and 7g PAN were dissolved in 55g DMF to prepare PVDF-PAN spinning solution, which was stirred at room temperature for 24h to obtain PVDF-PAN mixed solution. The spinning rate was 1.2ml / h, the voltage was set to 20KV, the ambient humidity (RH) was ≤30%, the distance between the spinning nozzle and the receiving plate was 20cm, the solution was collected by roller, and dried at 70℃ for 2.5h to obtain PVDF-PAN electrospinning film.
[0051] Li2CO3:AlOOH:TiO2:NH4H2PO4 was added with anhydrous ethanol in a planetary ball mill according to a molar ratio of 1.3:0.3:1.7, and the mixture was dried at 80°C for 5 hours to obtain a precursor material. The precursor was first heated to 300°C in a muffle furnace at a heating rate of 5°C / min and calcined for 2 hours, then heated to 700°C and calcined for 4 hours, and then naturally cooled to room temperature. The calcined LATP block material was taken out, ground, and sieved (100 mesh) to obtain LATP [Li 1.3 Al 0.3 Ti 1.7 (P04)3] Powder.
[0052] A mixed solution of DMF and anhydrous ethanol was prepared in a mass ratio of 2:1, and LATP nanomaterials were added into the mixed solution with a content of 15%. The mixture was dispersed by magnetic stirring to obtain LATP slurry.
[0053] Weigh 2g of polyethylene glycol and 120g of distilled water and stir at 70°C for 20min to mix them evenly. Add 7g of PVDF powder to the mixed material and stir for 2h to obtain a PVDF dispersion. Subsequently, add 1g of an aqueous non-ionic fluorocarbon surfactant and 1g of an aqueous adhesive and stir evenly. Filter with a magnetic filter and a 100-mesh filter to obtain an aqueous PVDF slurry.
[0054] The base film is sprayed and coated with a spraying machine (the coating thickness of the LATP slurry is 2 μm, and the spraying thickness of the PVDF slurry is 2 μm), dried, and rolled up to obtain a composite diaphragm.
[0055] [Example 2]
[0056] The difference from Example 1 is that 5 g PVDF and 5 g PAN are dissolved in 55 g DMF to prepare a PVDF-PAN spinning solution.
[0057] [Example 3]
[0058] The difference from Example 1 is that 7 g PVDF and 3 g PAN are dissolved in 55 g DMF to prepare a PVDF-PAN spinning solution.
[0059] [Example 4]
[0060] The difference from Example 2 is that 1 g PVDF and 9 g PAN are dissolved in 55 g DMF to prepare a PVDF-PAN spinning solution.
[0061] [Example 5]
[0062] The difference from Example 2 is that 9 g PVDF and 1 g PAN are dissolved in 55 g DMF to prepare a PVDF-PAN spinning solution.
[0063] [Example 6]
[0064] The difference from Example 2 is that the amount of LATP nanomaterial added is 10%.
[0065] [Example 7]
[0066] The difference from Example 2 is that the amount of LATP nanomaterial added is 20%.
[0067] [Example 8]
[0068] The difference from Example 2 is that the amount of LATP nanomaterial added is 25%.
[0069] [Comparative Example 1]
[0070] The difference from Example 2 is that the LATP slurry and PVDF slurry are not modified.
[0071] [Comparative Example 2]
[0072] It is a commercial PP diaphragm, denoted as PP.
[0073] [Comparative Example 3]
[0074] For the commercial PP separator, the amount of LATP nanomaterial added is 15%, recorded as PP-1.
[0075] The above embodiments and comparative examples were subjected to liquid absorption test, porosity test and thermal shrinkage test, and the test methods are as follows:
[0076] Liquid absorption rate test: Calculate the liquid absorption rate of the composite diaphragm based on the mass change after the diaphragm absorbs the electrolyte.
[0077] First, in an argon-filled glove box, weigh the mass M1 of a 16μm thick 5cm×5cm diaphragm, soak the diaphragm in an electrolyte (1mol / LLiPF6 / EC+DMC+EMC, volume ratio 1:1:1) for 3h, take it out, wipe the residual electrolyte on the surface of the diaphragm with filter paper, and weigh it again (M2). The liquid absorption rate W of the diaphragm is calculated according to formula (1):
[0078] W=(M2-M1) / M1×100% (1)
[0079] Porosity test: The test is carried out by physical method, that is, the volume change of the diaphragm after immersion in n-butanol liquid for 2 hours is used for calculation. The porosity Q of the diaphragm is calculated according to formula (2):
[0080] Q=(M3-M4) / ρV×100% (2)
[0081] In formula (2), M3 is the dry mass of the diaphragm before immersion, g; M4 is the wet mass of the diaphragm after immersion, g; ρ is the density of n-butanol, 0.8098 g / cm 3 ; V is the apparent volume of the composite diaphragm dry film, cm 3 .
[0082] Heat shrinkage test: stack the membrane into 3 layers, flatten them, exhaust the air between the membranes, take out the cutting board (300*100), cut out the membrane sample, and measure the length A1 and width B1 of the cut sample. Set the oven temperature to 130℃, and keep it warm for 1 hour after reaching the temperature. Put the sample in the oven and keep it warm for 1 hour. After cooling for 10 minutes, measure the length A2 and width B2 of the sample.
[0083] Longitudinal thermal shrinkage of diaphragm = (A1-A2) / A1*100% (3)
[0084] Transverse thermal shrinkage of diaphragm = (B1-B2) / B1*100% (4)
[0085] The test results are shown in Table 1.
[0086] Table 1
[0087]
[0088] Further comparison of the porosity performance of the two membranes shows that the liquid absorption rate of the membrane is positively correlated with the porosity. The porosity of the PVDF-PAN composite membrane modified by LATP and PVDF increases significantly. This is because after loading nano-LATP particles and PVDF particles, the membrane is provided with more specific surface area and pore structure, thereby increasing the liquid absorption mass of the composite membrane and showing a better liquid absorption rate. The greater the liquid absorption rate, the more electrolyte is retained on the membrane, the smaller the interface internal resistance between the membrane and the electrode, and the more Li+ can be promoted. + Rapid transmission between the positive and negative electrodes. In addition, the thermal shrinkage of the composite diaphragm and PP film in this application at 130°C for 1 hour is reduced, indicating that the stability of the composite diaphragm is improved and the ability to resist thermal shrinkage is enhanced after adding high-temperature stable LATP nanoparticles and PVDF particles.
[0089] Although the above describes the illustrative specific implementation methods of the present application so that technicians in this technical field can understand the present application, the present application is not limited to the scope of the specific implementation methods. For ordinary technicians in this technical field, as long as various changes are within the spirit and scope of the present application defined and determined by the attached claims, all application creations using the concept of the present application are protected.
Claims
1. A composite diaphragm, characterized in that: include: A base film, wherein the base film is an electrospun film, and the electrospun film is made by electrospinning an electrospinning solution, wherein the electrospinning solution includes a polymer mixture; A first coating layer, wherein the first coating layer is disposed on one side surface of the base film, and the first coating layer is formed by coating with a nano coating; the thickness of the first coating layer is 2 μm; A second coating layer, wherein the second coating layer is disposed on the other side surface of the base film, the second coating layer is formed by spraying PVDF slurry, and the thickness of the second coating layer is 2 μm; The polymer mixture includes polyvinylidene fluoride and polyacrylonitrile; The mass ratio of the polyvinylidene fluoride to the polyacrylonitrile is 1:
1.
2. A composite diaphragm according to claim 1, characterized in that: The nano coating has a NASICON type structural system.
3. A composite diaphragm according to claim 1, characterized in that: The nano coating is LATP slurry.
4. A composite diaphragm according to claim 3, characterized in that: The LATP slurry contains 10-25wt% of LATP nanomaterial.
5. A composite diaphragm according to claim 1, characterized in that: The PVDF slurry contains 1-10 wt % of a base material.
6. A composite diaphragm according to claim 5, characterized in that: The base material comprises PVDF powder, water-based adhesive, surfactant and dispersant.
7. A method for preparing a composite diaphragm according to claim 1, characterized in that: The following steps are involved: Preparation of electrospinning film: drying the powdered polymer mixture and adding it to a solvent N,N-dimethylformamide, stirring to fully disperse it to obtain an electrospinning solution, and performing electrospinning in an electrospinning device to obtain the electrospinning film; Preparation of nano coating: preparing a mixed solution of DMF and anhydrous ethanol, adding LATP nanomaterial into the mixed solution, stirring and dispersing, and preparing the nano coating; Preparation of PVDF slurry: heat and stir the dispersant and distilled water at 40-80°C for 10-60 minutes to completely mix them, add PVDF powder to the mixed material, stir for 0.5-4 hours to obtain a PVDF dispersion, then add an aqueous binder and a surfactant, stir evenly, and filter with a magnetic filter and a 100-mesh filter to obtain the PVDF slurry; Preparation of the composite membrane: coating the nano coating on one side of the electrospun film, and spraying the PVDF slurry on the other side of the electrospun film to obtain the composite membrane.
8. The method for preparing a composite diaphragm according to claim 7, characterized in that: The electrospinning equipment adopts a spinning rate of 0.2-1.2 ml / h, a voltage of 14-20 KV, an environmental humidity of ≤30%, a distance between the spinning nozzle and the receiving plate of 10-20 cm, and is collected by a roller and dried at 50-80° C. for 1-3 hours.
9. The method for preparing a composite diaphragm according to claim 7, characterized in that: The LATP nanomaterial is prepared by the following method: Li2CO3, AlOOH, TiO2, and NH4H2PO4 powders are added into anhydrous ethanol, and then mixed on a planetary ball mill to obtain a precursor material; the precursor material is calcined in a muffle furnace, and the LATP nanomaterial is obtained through grinding and sieving.
10. The method for preparing a composite diaphragm according to claim 9, characterized in that: The molar ratio of Li2CO3:AlOOH:TiO2:NH4H2PO4 in the precursor material is 1.3:0.3:1.7:
1.
11. The method for preparing a composite diaphragm according to claim 10, characterized in that: The temperature in the muffle furnace is first raised to 200-300° C. at a heating rate of 2-5° C. / min and calcined for 2-4 hours, then raised to 600-800° C. and calcined for 3-5 hours, and then naturally cooled to room temperature.
12. The method for preparing a composite diaphragm according to claim 7, characterized in that: The mass ratio of the DMF to anhydrous ethanol is 2:
1.
13. The method for preparing a composite diaphragm according to claim 7, characterized in that: In the PVDF slurry, the mass ratio of PVDF powder, aqueous binder, surfactant and dispersant is 65-85:3-10:1.5-5:8-20.
14. A battery, characterized in that: A diaphragm is provided, wherein the diaphragm is made of the composite diaphragm according to any one of claims 1 to 13.
15. An object, characterized in that The object comprises a battery as claimed in claim 14.
16. An object according to claim 15, characterized in that The object is an electronic product or a vehicle.
Citation Information
Patent Citations
A kind of electrospinning method prepares the method for high thermal stability anti-overcharge battery diaphragm
CN105552279B
PVDF-coated lithium-ion battery separator and preparation method thereof
CN105552277A
Inorganic-organic nano composite solid electrolyte membrane and preparation method and application thereof
CN109638349A
Sodium-ion battery diaphragm and preparation method thereof
CN110120483A
Battery separator with lithium-ion conductor coating
WO2019246263A1